Relationship between Real Exchange Rate and Economic Growth: the case of South Africa - Patel, Deeviya; Mah, Gisele (Journal of Economics and Behavioral Studies, 2018)
The objective of this study was to investigate the relationship between real exchange rate and economic growth in South Africa. Using time series data, the period from 1980 to 2015 was covered in the study. Data was collected from the South African Reserve Bank, the International Monetary Fund and International Financial Statistics. The Johansen cointegration and the Vector Error Correction Model estimation techniques were employed in the study, followed by VEC Granger causality test, variance decomposition and impulse response function. The long-run results revealed a negative and significant relationship between real exchange rate with export and economic growth. On the other hand, money supply and foreign direct investment have a positive and significant relationship with real exchange rate. Only export was significant and positively related to real exchange rate in the short-run. Results of granger causality showed that only export granger causes real exchange rate thus, a unidirectional causality exists between export and real exchange rate. Results of variance decomposition revealed that the real exchange rate is highly affected by shocks from economic growth. The impulse response functions showed that real exchange rate responds positively to shocks from real exchange rate and money supply. On the contrary, real exchange rate responds negatively to a shock from economic growth. There is, therefore, a need to increase exports, money supply, foreign direct investment and economic growth as these would lead to an increase in the Rand and consequently, appreciation of the Rand.